Contribuições do planejamento estratégico na gestão de organizações do terceiro setor - (:unkn) unknown (Universidade Federal do Pampa, 2010)
The organizations that constitute the third sector rend services aiming at a better population’s quality of life. Recently, this sector gained as great social importance and as economics, being necessary the excellence of the administration on those corporations, so that they can keep competitive. This study aims to verify how strategic planning can contribute in the third sector organizations management. For this reason, two different situations concerning strategic planning were analyzed. The methodology used to develop the study was divided as to ends and means. Having been characterized as descriptive and comparative research in relation to the purposes and Documentary and Field in relation to their means. The main issue was addressed in a qualitative way. Data were collected through semi-structured interviews with presidents of two philanthropic organizations. From the results analysis, it was verified that an organization that puts a strategic planning on practice can establish its goals and the ways to reach them, as well as formulate and implement successfully its strategies. An organization that does not put a strategic planning in action plans its goals, although it does not plan how to achieve them. Moreover, it can formulate strategies and can not have a vision for the future.Therefore, it was evidenced that such management instrument contributes to the development of social organizations, while it allows the organization vision for the future, the implementation of quality programs and reaching more beneficiaries. On the other hand, the absence of this instrument restrains the knowledge about the environment those organizations are in, making difficult the expansion about target audience, services rended, ways of fundrising, financial sustainability and partnership with other organizations or other sectors in the society, raising difficulties to its competitive development.
Contributions of strategic planning in the management of third sector organizations
Keywords: Planejamento estratégico; Terceiro setor; Planejamento estratégico no terceiro setor; Strategic planning; Third sector; Strategic planning in the third sector; CNPQ::CIENCIAS SOCIAIS APLICADAS